Toll like receptor 4 facilitates invasion and migration as a cancer stem cell marker in hepatocellular carcinoma. Issue 2 (28th March 2015) - Liu, Wen-Ting; Jing, Ying-Ying; Yu, Guo-feng; Han, Zhi-peng; Yu, Dan-dan; Fan, Qing-Min; Ye, Fei; Li, Rong; Gao, Lu; Zhao, Qiu-Dong; Wu, Meng-Chao; Wei, Li-Xin
Highlights TLR4 expression was associated with the ability of invasion and migration in HCC. TLR4 expression contributes to the stem-like properties of HCC cells. The high expression of TLR4 is associated with clinicopathological characteristics and prognosis of HCC.